MODELO DE AVALIAÇAO E DESENVOLVIMENTO DE FORNECEDORES PARA EMPRESA DO SETOR ELÉTRICO DA ADMINISTRAÇÃO PÚBLICA - Evaristo, Samanta Katia de Oliveira (2013)
This research proposes a model for government procurement assessment and development that complies with brazilian laws. The model is used to improve the procurement management system used in a government-owned electrical through systematic assessment of their supply chain. The case study is used based on literature research on the following topics: basic legislation on public procurement and contracting, procurement, supply management, vendor supply chain, supplier management, role of supplier performance evaluation supplier, sustainability and sustainable procurement. Interviews are conducted with government procurement personnel of the main electricity companies in Brazil. Search results provide consistent information in order to support the procurement department of the company used in this study in effective decision making regarding the use of the proposed model.